Cell death biomarker M65 is a useful indicator of liver inflammation and fibrosis in chronic hepatitis B: A cross-sectional study of diagnostic accuracy. Issue 20 (May 2017) - Wei, Xinhuan; Wei, Hongshan; Lin, Wei; Hu, Zhongjie; Zhang, Jing
Abstract : Abstract: Cell death markers, M65 and M30, have been suggested to be sensitive markers of liver inflammation and fibrosis in nonalcoholic fatty liver disease and chronic hepatitis C. Our aim was to investigate whether these markers were useful in diagnosing liver inflammation and fibrosis in chronic hepatitis B (CHB). We examined 186 patients with CHB; 18 sex- and age-matched healthy subjects were controls. The blood samples were collected from CHB patients within 1 week before or after liver biopsy. According to METAVIR score system, liver inflammation was graded from A0 to A3, and fibrosis from F0 to F4. Serum M65 and M30 levels were in parallel with the grades of liver inflammation. M65, not M30, increased significantly in patients with severe inflammation and normal alanine aminotransferase. M65 is one of the independent predictors of severe liver inflammation (≥A2). The levels of M65 and M30 levels significantly increased in parallel with the degree of inflammation in F1 patients, whereas they showed no statistical difference between different stages of fibrosis in A1 patients. Serum M65 is a useful indicator of liver inflammation in CHB patients. Serum M65, not M30, is valuable in the grading of liver fibrosis.